2016
DOI: 10.1556/2006.5.2016.032
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Treatment-Seeking British Pathological Gamblers

Abstract: Background and aimGambling is a widespread recreational activity in the UK. A significant percentage of gamblers develop subclinical or clinically relevant problem gambling issues, but only a low percentage of them seek treatment. Although characteristics of pathological gamblers from treatment-seeking population have been examined in some research, only a few studies have explored the differences between females and males. This study aimed to examine the gender-related differences in demographics, gambling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 39 publications
4
43
0
Order By: Relevance
“…This study also found that the median age in females seeking care for pathological gambling and co‐occurring conditions was significantly greater than in males. This study finding concurs with prior research that found that while onset of pathological gambling occurs later in life in females compared to males they developed gambling disorders faster than males …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study also found that the median age in females seeking care for pathological gambling and co‐occurring conditions was significantly greater than in males. This study finding concurs with prior research that found that while onset of pathological gambling occurs later in life in females compared to males they developed gambling disorders faster than males …”
Section: Discussionsupporting
confidence: 93%
“…Male gender was identified as a risk factor for alcohol dependence in pathological gamblers . This study found that a significantly greater proportion of males than females had an alcohol dependence syndrome disorder and a greater number of episodes of care in males compared to their counterparts without the condition, suggesting that alcohol dependence syndrome might be a gender‐specific risk factor to consider for screening and implementing effective disordered gambling prevention strategies.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Gender differences found in the two scales deserve further discussion. In fact, such differences confirm what found in previous studies (Casey et al 2008;Dunsmuir et al 2018;Raylu and Oei 2004b;Ronzitti et al 2016;Smith et al 2015a), namely that males tend to score higher than females at the GUS, and females tend to score higher than males at the GRSEQ. These results seem to support evidence that male adults are more likely to develop and maintain problem gambling behavior than female adults, possibly due to higher risk-taking and social anxiety, as discussed in recent literature (Wong et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Gender differences are known in the literature, with males usually presenting higher levels of gambling-related cognitions and behaviors than females (Ronzitti et al 2016). McNeilly and Burke (2001) hypothesized that those differences may be due to the fact that males tend to be more affected by social anxiety than females, ultimately determining an increase in attractivity of gambling-related activities.…”
mentioning
confidence: 99%